The inverse relation of pre-nuclear and nuclear prominences in German - Simon Roessig (Laboratory Phonology)
The importance of pre-nuclear prominences for focus marking has been largely neglected. Recent studies, however, present first evidence that the prosody of the pre-nuclear region indicates its status as part of a broad focus or as pre-focal. This study presents a systematic investigation of the pre-nuclear domain and its relation to the nuclear accent in German. The results show that the realization of the pre-nuclear domain indeed depends on whether it is focal or pre-focal: The pre-nuclear noun is characterized by larger F0 excursions, higher F0 maxima and larger durations when it is in broad focus than when it precedes a narrow focus. Furthermore, the realization of a pre-focal, pre-nuclear domain depends on the following focus: The pre-nuclear noun is produced with smaller F0 excursions, lower F0 maxima and shorter durations before a corrective focus than before a non-corrective narrow focus. The comparison to the nuclear accent suggests an inverse relationship, i.e., the pre-nuclear domain becomes less prominent when the nuclear domain becomes more prominent. The findings suggest that the phonetic manifestation of information structure is distributed over larger prosodic domains and entails the modulation of phrasal prominence profiles rather than just local adjustments of the nucleus.